Enhancing the Professionalism of Indonesian National Police Personnel through the Live in Program in the Education of Female Police Non-Commissioned Officers: A Systematic Literature Review - Mawar Runiasih; Masduki Ahmad; Desi Rahmawati; Kamaludin Kamaludin; Cynthia Mayang Sari (Journal of Educational Sciences, 2026)
Enhancing the professionalism of Indonesian National Police (POLRI) personnel has become increasingly important in responding to the growing demands for humanistic public service and social adaptability. One of the strategic approaches implemented in police education is the Live In program within the training of Female Police Non-Commissioned Officers (Bintara Polwan), which emphasizes experiential learning through direct community engagement. This study aims to systematically analyze the effectiveness of the Live In program in strengthening professionalism, particularly in developing empathy, social awareness, and adaptive competencies. This research employs a Systematic Literature Review (SLR) approach based on PRISMA 2020 to synthesize relevant empirical and theoretical evidence. A total of 250 records were identified from major academic databases, resulting in 45 selected studies after a rigorous screening and eligibility process. The findings reveal that the Live In program significantly contributes to the development of humanistic character, interpersonal competence, and gender-sensitive soft skills, and is more effective than conventional training approaches in fostering professional attitudes and social responsibility. The study concludes that structured implementation, institutional support, and standardized evaluation mechanisms are essential to maximize program outcomes and support holistic police education.